geog.1 : 4th edition geography for key stage 3 - Gallagher, RoseMarie; Parish, Richard; Williamson, Janet (Oxford : Oxford University Press, 2014)
geog.123 is a three-book course for the National Curriculum at Grade 6-9. This 4th edition has been specially written to match the new Programme of Study (for teaching from 2014).geog.123 combines a rigorous approach to content with a light touch, making it the most effective and engaging Grade 6-9 course available.Easy-to-use double-page spreads feature clearly-written objectives, student-friendly language, illustrated step-by-step explanations, up-to-date case studies and place-based examples, and high-quality photos, maps, and diagrams. Each Student Book has a glossary and full index.geog.1 includes coverage of the geological timescale, mapskills, the UK, glaciation, rivers, and Africa.Each Student Book is supported by online lesson plans and presentations, online resources including animations, and worksheets, and online assessment materials; an online Student Book; a Teacher's Handbook; a Workbook; and a Workbook Answer Book.